Iron-Chelating Agent Can Maintain Bone Homeostasis Disrupted by Iron Overload by Upregulating Wnt/Beta-Catenin Signaling. (27th May 2020) - Xu, Wei; Yu, Ronghua; Zhu, Xiaodong; Li, Zhikun; Jia, Jianjun; Li, Dachuan; Chen, Yu; Zhang, Xiangyang
Abstract : Background . The incidence of osteoporotic fractures is increasing. In this study, we explored the activities of Wnt/ β -catenin signaling in bone tissues with iron accumulation. Methods . We established rat bipedal walking models (RBWM), and a portion of our RBWM rats were intraperitoneally injected with ferric ammonium citrate, normal saline, and deferoxamine. Bone mineral density was measured with a small animal in vivo imaging system. The protein levels of ferritin, TRAP-5B, RANKL, and OPG in serum were measured by the enzyme-linked immunosorbent assay (ELISA). Quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot were used to quantify the RNA and protein expression levels of certain regulators involved in Wnt/ β -catenin signaling in bone tissues. Results . In the present study, we established a rat bipedal walking model containing 32 bipedal rats, which were randomly classified into four groups, termed as NS, FAC, FAC+NS, and FAC+DFO. Those three experimental groups with FAC injection had significantly lower bone mineral density (BMD) than the control group NS (P < 0.05 ). The disruption of bone homeostasis and downregulation of Wnt/ β -catenin signaling were also observed in the three groups with FAC injection. Moreover, after the injection of deferoxamine, those aberrations in samples with FAC injection seemed repaired as test results returning or getting close to normal ranges. Conclusion . The osteoporosis could be caused by iron overload, which reduced the bone mineral density by disrupting the homeostasis of bone formation and absorption and attenuating the Wnt/ β -catenin signaling in bone tissues. The deferoxamine had the potential to improve the bone health by reducing the accumulation of iron and increasing the bone mass, which might be a promising therapeutic solution for osteoporosis.